Evaluation of clinical assessment methods for scapular dyskinesis - Uhl, Tim L; Kibler, W Ben; Gecewich, Ben; Tripp, Brady L (Arthroscopy, 2009)
The purposes of this study were to (1) assess the inter-rater reliability and validity of 2 clinical assessment methods of categorizing scapular dyskinesis and (2) quantify the frequency of asymmetry of bilateral scapular motion in injured and uninjured shoulders by use of 3-dimensional (3D) kinematic analysis. We evaluated 56 subjects, 35 with shoulder injury and 21 with no symptoms. Two blinded evaluators categorized the scapular motion of all subjects to determine inter-rater reliability using 2 observational methods ("yes/no" and "4 type") to evaluate scapular dyskinesis. Subjects were also instrumented with electromagnetic receivers to assess bilateral 3D scapular kinematics to determine the presence of dyskinesis and establish criterion validity of the 2 methods. The inter-rater percent agreement and the degree of this agreement as measured by kappa statistic showed that the yes/no method produced a higher inter-rater percent agreement (79%, kappa = 0.40) than the 4-type method (61%, kappa = 0.44). The yes/no method had a higher sensitivity (76%) and positive predictive value (74%) when compared with the 3D criterion. A chi(2) analysis found significantly more multiple-plane asymmetries in symptomatic subjects (54%) in flexion compared with asymptomatic subjects (14%) (P = .002). The yes/no method allows multiple-plane asymmetries to be considered in clinical assessment and therefore renders this a good screening tool for the presence of scapular dyskinesis. Kinematic analysis shows that asymmetries are common in symptomatic and asymptomatic populations. Testing in flexion showed a higher frequency of multiple-plane scapular asymmetries in the symptomatic group. Identification of scapular dyskinesis is a key component of the shoulder examination. The clinician's ability to establish the presence or absence of scapular dyskinesis by observation is enhanced using a simple yes/no method especially when testing subjects in shoulder forward flexion. Although scapular asymmetries appear to be a prevalent finding, dyskinesis in the presence of shoulder symptoms should be considered a potential factor contributing to the dysfunction in the presence of shoulder symptoms should be considered a potential factor contributing to the dysfunction.